The Effect of Video-Based Health Education on Improving Students’ Knowledge of Helminthiasis Prevention - Hasjuni, Wira; Hamdan, Dian Furqani (CV. Social Politic Genius (SIGn), 2024)
Infections caused by Soil-Transmitted Helminths (STH) remain a major public health issue in Indonesia, particularly among primary school students. This high prevalence is closely associated with poor personal hygiene practices driven by a lack of knowledge about prevention (a predisposing factor). This study aimed to analyze the effect of video-based health education on improving students’ knowledge regarding helminthiasis prevention at SDN 101 Salu Simbuang, Luwu Regency. A quantitative pre-experimental approach with a one-group pretest-posttest design was utilized. A total of 30 students were selected through stratified sampling to serve as respondents. Primary data were collected using a structured questionnaire to measure knowledge before (pretest) and after (posttest) the intervention. Data were analyzed using the Wilcoxon Signed-Rank Test (α = 0.05). The results revealed a substantial increase in the students’ mean knowledge score from 5.00 (SD = 0.788) at baseline to 7.63 (SD = 0.615) post-intervention. The statistical analysis confirmed that this improvement was highly significant (p < 0.001). Item analysis identified significant improvements across most prevention concepts, although understanding of specific handwashing procedural details showed no improvement (remaining at 50.00% incorrect). In conclusion, video-based health education significantly and effectively improves primary school students’ knowledge (predisposing factors) of helminthiasis prevention, making it a highly recommended health promotion tool in school settings.